Increased Appetite Plays a Key Role in Olanzapine-Induced Weight Gain in First-Episode Schizophrenia Patients - Huang, Jing; Hei, Gang-Rui; Yang, Ye; Liu, Chen-Chen; Xiao, Jing-Mei; Long, Yu-Jun; Peng, Xing-Jie; Yang, Yi; Zhao, Jing-Ping; Wu, Ren-Rong (Frontiers in Pharmacology, 2020)
Weight gain and metabolic disturbances, potentially influenced by increased appetite, are common effects of olanzapine treatment in patients with schizophrenia. In this study, we explored the association between olanzapine-induced weight gain and metabolic effects with increased appetite. Drug-naïve, first-episode schizophrenia patients were treated with olanzapine for 12 weeks. Assessments included time to increased appetite, body weight, body mass index, biochemical indicators of blood glucose and lipids, proportion of patients who gained more than 7% or 10% of their baseline weight upon treatment conclusion, patients who developed dyslipidemia, and Positive and Negative Syndrome Scale scores. In total, 33 patients with schizophrenia receiving olanzapine were enrolled and 31 completed the study. During the 12-week olanzapine treatment, 77.4% (24/31) patients had increased appetite with 58.1% (18/31) patients having increased appetite within the first 4 weeks. The mean time for increased appetite was 20.3 days. More patients in the increased appetite group increased their initial body weight by more than 7% after 12 weeks when compared to patients with unchanged appetite (22/24 [91.7%] vs. 3/7 [42.9%], p = 0.004). Earlier increased appetite led to more weight gain during the following month. Overall, 50% of patients in the increased appetite group had dyslipidemia after 12 weeks. Our results demonstrated that olanzapine induced significantly appetite increase in first-episode patients with schizophrenia and appetite increase played a key role in olanzapine-induced weight gain and dyslipidemia. Clinical Trial Registration NCT03451734. Registered March 2, 2018 (retrospectively registered).